ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI KENTANG GRANOLA DI DESA WONOKERSO KABUPATEN PROBOLINGGO - Sheliena, Esther; Hanani, Nuhfil; Riana, Fitria Dina (Jurnal Dinamika Sosial Ekonomi, 2024)
Potato is one of the staple food for humans and the most popular agricultural crops that are widely cultivated in Indonesia. This horticultural commodity plays an important role as food, contributes to health and environmental aspects, and is a source of income for farmers. The potato variety most widely used by potato farmers is the Granola variety. The obstacles faced by potato farmers are limited capital and high production costs. Limited production factors for potato farmers and expensive production costs are considerations in maximizing farming profits. This research aims to analyze the income and feasibility of farming by potato farmers located in Wonokerso Village, Probolinggo Regency. The sample for this research consisted of 42 respondents who were farmers of the granola variety potato in Wonokerso Village, who were determined using a simple random sampling technique. The data obtained in this research was analyzed quantitatively in the form of production costs, revenues and income. The results of this research show that the average production of potato granola farming in Wonokerso Village is 9,289 kg/ha/planting season. The income from granola potato farming at the research location per planting season is IDR. 53,659,527. This farming business is worth pursuing because it provides benefits to farmers with R/C ratio and B/C ratio values of more than 1.